Propuesta de elaboración de un producto turístico en la parroquia Hualtaco, cantón Huaquillas, provincia de El Oro - Merchán Barros, Brigitte Elizabeth (2016)
The final graduate research project aims to develop a service proposal focused in a productive tool for diversifying economy in Hualtaco, Huaquillas, El Oro province. First of all, tourism is part of this service proposal as a productive tool for economic revival in this sector. Secondly, this touristic product proposal is based on a microcircuit called “La Travesía del Manglar”. This microcircuit promotes a different touristic offer with tourist facilities, incredible natural and unique cultural tourist attractions in the coastal region of Ecuador. On the other hand, this project has used a specific research process: Descriptive research Qualitative methodology Semi-structured interviews the interviews aim at territorial technicians, local people and local partners As a result of this research is that one of the mayors and authorities objectives is to prioritize tourism, taking advantage of the identified tourist potential for the benefit of Hualtaco. Similarly, the actors identified in the research formed by the population and local partners, accept tourism as an alternative to diversify the production of the sector. Finally, for this reason this service proposal has a significant level of importance for this sector because it will promote an economic recovery. Also, this project unifies the identified local actors with the touristic potential in Hualtaco.